Persepsi Stakeholder Mengenai Kesiapan Sarana Prasarana Kecamatan Kotabumi Menjadi Kawasan Perkotaan - Adelia Azis; Rahayu Sulistiyorini; Fembriarti Erry Prasmatiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Kotabumi Sub-district serves as the administrative center and main activity hub of North Lampung Regency and has functionally exhibited characteristics of an urban area. However, this development needs to be supported by adequate readiness of facilities and infrastructure to ensure that the transformation toward an urban area can proceed optimally and sustainably. Differences in perceptions between the community and the government regarding the condition of facilities and infrastructure are important to examine as a basis for formulating appropriate development strategies. This study aims to analyze stakeholder perceptions regarding the readiness of facilities and infrastructure in Kotabumi Sub-district to become an urban area, to identify gaps between existing conditions and ideal conditions based on the requirements of the Indonesian National Standard (SNI) for Urban Residential Environment Planning and the Regional Medium-Term Development Plan (RPJMD) of North Lampung Regency, and to formulate suitable area development strategies. The research employed a mixed-methods approach combining quantitative and qualitative methods. Quantitative data were obtained through Likert-scale questionnaires capturing community and government perceptions and were analyzed using descriptive analysis and gap analysis. Stakeholder interviews were conducted to strengthen the formulated strategies. In addition, a precedent study of district-level urban areas was used as a reference in developing the strategies. The results indicate that the readiness of facilities and infrastructure in Kotabumi Sub-district falls within the category of ready toward optimal. Government, education, health, and trade and service facilities are considered to function relatively well; however, gaps remain in terms of service quality and equitable distribution. Meanwhile, cultural and recreational facilities, green open spaces, and environmental infrastructure such as sanitation, solid waste management, and drainage show relatively lower levels of readiness and are therefore prioritized for development. The study concludes that Kotabumi Sub-district has the potential and basic readiness to be developed as an urban area; however, improvements in the quality, equity, and integration of facilities and infrastructure are required through integrated planning, synergy among stakeholders, and spatial use control to meet urban area standards optimally and sustainably.